Bedah Rumpon : The Cultural Tradition of Fishing in the Ajibarang Community of Banyumas - Muhammad Zainuddin; Muh. Sulaiman Dadiono; Wiwiet Teguh Taufani (PT. Gyandharma Global Media, 2025)
The tradition of